Micro-structured fluid within a channel under static and oscillatory pressure gradients: A novel Darcy-Forchheimer flow investigation - Yijie Li; Kashif Ali; Sohail Ahmad; Shahzad Ahmad; Wasim Jamshed; Assmaa Abd-Elmonem; Ayesha Amjad; Sayed M. El Din (Engineering Science and Technology, an International Journal, 2023)
The pertinence and importance of Darcy-Forchheimer flows can be found in large spectrum of engineering, biological and technological mechanisms like solar absorption and filtration, drainage problems, solar cells, ground stream hydrology, solar panels, irrigation and so forth. The major concern of this study is to interpret that how much a Darcy-Forchheimer flow of a micro-structured fluid (e.g., micropolar fluid) within a channel is influenced by the combined effects of static and oscillatory pressure gradients. Numerical treatment is carried out via three steps explicit Runge-Kutta method. Impacts of the preeminent parameters on the flow, mass and heat transport features of the problem are over looked by means of graphical and tabular representations. The numerical consequences evidently point out that the influence of oscillatory component is to elevate the fluid velocity whereas static component of pressure gradient tends to decelerate the velocity inside the channel. It is also determined here that Darcy parameter sufficiently reduces the angular velocity in the flow regime.